Relativistic drag forces on black holes from scalar dark matter clouds of all sizes - Traykova, D; Vicente, R; Clough, K; Helfer, T; Berti, E; Ferreira, PG; Hui, L (American Physical Society, 2023)
We use numerical simulations of scalar field dark matter evolving on a moving black hole background to confirm the regime of validity of (semi)analytic expressions derived from first principles for both dynamical friction and momentum accretion in the relativistic regime. We cover both small and large clouds (relative to the de Broglie wavelength of the scalars), and light and heavy particle masses (relative to the black hole size). In the case of a small dark matter cloud, the effect of accretion is a non-negligible contribution to the total force on the black hole, even for small scalar masses. We confirm that this momentum accretion transitions between two regimes (wave and particlelike) and we identify the mass of the scalar at which the transition between regimes occurs.